Earnings Inequality and the Minimum Wage: Evidence from Brazil - Engbom, Niklas; Moser, Christian (American Economic Review, 2022)
Increases in the minimum wage can substantially reduce earnings inequality. To demonstrate this, we combine administrative and survey data with an equilibrium model of the Brazilian labor market. We find that a 128 percent increase in the real minimum wage in Brazil between 1996 and 2018 had far-reaching spillover effects on wages higher up in the distribution. The increased minimum wage accounts for 45 percent of a large fall in earnings inequality over this period. At the same time, the effects of the minimum wage on employment and output are muted by reallocation of workers toward more productive firms.. (JEL D31, E23, E24, J31, J38, O15)